Hyperphosphatemic Familial Tumoral Calcinosis Hidden in Plain Sight for 73 Years: A Case Report - Lee, Alisa E.; Hartley, Iris R.; Roszko, Kelly L.; Vanek, Chaim; Gafni, Rachel I.; Collins, Michael T. (Frontiers in Dental Medicine, 2021)
While dental pulp calcifications and root anomalies may be inconsequential incidental findings in dental radiographs, they can, especially in combination, represent a clue, hidden in plain sight, for the diagnosis of hyperphosphatemic familial tumoral calcinosis (HFTC). HFTC is an autosomal recessive disease of mineral metabolism characterized by sometimes massive, painful calcification around large joints, systemic inflammation, dental pulp calcification, and thistle-shaped roots. This paper describes a woman with HFTC who endured not only the symptoms of HFTC for decades, but also the frustration of not knowing the cause. The diagnosis was finally made at the age of 73 years, when the connection between a large right shoulder calcification and hyperphosphatemia was made. The dental findings were likely present on her initial radiographs taken in childhood. Increased awareness of the association between characteristic dental findings and HFTC may allow for earlier diagnosis and interventions to improve the care of patients with this rare condition.